Effectiveness of Structured Teaching Program on Knowledge among the Anganwadi Workers Regarding Behavioral Problems of Pre-schoolers - Kale, Alpana; Salve, Priyanka (International Journal of Nursing Research, 2023)
Aim and Objectives: The objective of this study was to assess the effectiveness of structured teaching program on knowledge among the Anganwadi workers (AWWs) regarding behavioral problems of pre-schoolers. The present study was carried out assess the knowledge among AWWs related to behavioral problems of pre-schoolers in selected rural areas and the effectiveness of structured teaching program among the AWWs regarding behavioral problems of preschoolers in selected rural areas along with its association. Materials and Methods: A total 100 AWWs were selected. The data were collected using structured knowledge questionnaires. The structured teaching program was administered on the day 1 followed the pre-test. On the 7th day, post-test was conducted to assess the gain in knowledge using the same structured knowledge questionnaire. Results: Findings revealed that highest percentage 34% of the sample are age between 41 and 50 year, 40% had completed higher secondary education, and majority of the AWWs 48% of the samples had work experience which is between 9 and 16 years. In the present study, the highest percentage 46% of the AWWs interaction with preschoolers was 7–8 times in a month. The pre-test knowledge score of AWWs revealed that majority 61% of AWWs had good (11–15) knowledge about behavioral problems of pre-schoolers. In post-test, majority of the AWWs 49% of AWWs had very good (16–20) and 49% of excellent (21–25) knowledge about behavioral problems in pre-schoolers. Findings show that the pre-test knowledge mean score was 12.13 and post-test mean score was 20.33, after structured teaching program. Conclusion: The present study shown that significant difference in the pre-test and post-test knowledge score of AWWs, which shows structured teaching program was effective.